2001
DOI: 10.1007/s00384-001-0362-7
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery for brain metastases from colorectal cancer

Abstract: SR for brain metastases from colorectal cancer results in a high local tumor control rate of 94% associated with few complications and therefore provides patients with a higher quality of their remaining life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…The median survival for all 49 patients was 5.1 months (range, 1-18 months), which is consistent with previous reports of patients with BM from CRC in which the median survival ranged from 2.8 months to 6 months. 11,17,21,22,27,28 Analysis of numerous prognostic factors in the current study identified age <65 years, shorter interval from CRC diagnosis to BM diagnosis, and >3 metastases as positive prognostic factors when they were considered as individual variables. However, 8 patients had >3 metastases, which limited our ability to reach a firm conclusion.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The median survival for all 49 patients was 5.1 months (range, 1-18 months), which is consistent with previous reports of patients with BM from CRC in which the median survival ranged from 2.8 months to 6 months. 11,17,21,22,27,28 Analysis of numerous prognostic factors in the current study identified age <65 years, shorter interval from CRC diagnosis to BM diagnosis, and >3 metastases as positive prognostic factors when they were considered as individual variables. However, 8 patients had >3 metastases, which limited our ability to reach a firm conclusion.…”
Section: Discussionmentioning
confidence: 82%
“…Two recent reports have retrospectively assessed the efficacy of SRS on BM from CRC. Schoeggl et al 22 reported the outcomes of 35 patients with CRC who underwent SRS for their BM; 13 of those 35 patients also received WBRT. They demonstrated a local control rate of 94%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, increased survival and improvement in clinical symptoms allowing greater functional dependence is achievable with both SR and SRS in select patients. 3,6,45,[58][59][60] It is important to emphasize, however, that patients who are considered for neurosurgical intervention are those who demonstrate good prognostic factors, and this selection bias may be responsible for the apparent success of surgical intervention in prolonging survival. Although the addition of WBRT does not significantly enhance postoperative survival following SR or SRS, it may reduce the likelihood of recurrence, increase the time to recurrence, and minimize the chance of death from neurologic complications.…”
Section: Discussionmentioning
confidence: 99%
“…70) who cannot tolerate surgery and have brain lesions <3.5 cm in diameter. 6,58,59 Although early treatment is linked to prolonged survival and improved quality of life, brain metastasis represents an advanced manifestation of GI cancer that is uniformly fatal.…”
Section: Discussionmentioning
confidence: 99%